ESC Working Group on Myocardial Function Position Paper: how to study the right ventricle in experimental models. (23rd February 2014) - Leite‐Moreira, Adelino F.; Lourenço, André P.; Balligand, Jean‐Luc; Bauersachs, Johann; Clerk, Angela; De Windt, Leon J.; Heymans, Stephane; Hilfiker‐Kleiner, Denise; Hirsch, Emilio; Iaccarino, Guido; Kaminski, Karol A.; Knöll, Ralph; et al.
<x xml:space="preserve">Abstract</x> The right ventricle has become an increasing focus in cardiovascular research. In this position paper, we give a brief overview of the specific pathophysiological features of the right ventricle, with particular emphasis on functional and molecular modifications as well as therapeutic strategies in chronic overload, highlighting the differences from the left ventricle. Importantly, we put together recommendations on promising topics of research in the field, experimental study design, and functional evaluation of the right ventricle in experimental models, from non‐invasive methodologies to haemodynamic evaluation and ex vivo set‐ups.